A bibliometric analysis of the current state and future directions of osteoporosis pharmacological treatment - Zhou, Xianxian; Xiong, Hua; Hu, Dexi (Frontiers in Medicine, 2025)
IntroductionOsteoporosis is a major health threat, particularly with the aging population in China. Medication remains a cornerstone of management, and bibliometric analysis can provide insights into current research status and future directions.MethodsRelevant literature from the Science Citation Index Core Collection (2015–2024) was analyzed using bibliometric methods. Visual maps were generated with Citespace 6.3R3 and VOSviewer 1.6.19 to assess research trends and hotspots.ResultsA total of 2,738 publications were included, showing a steady growth in research since 2015. The United States led in output, with the University of Toronto as the most productive institution. Brandi, Maria Luisa, and Kanis JA were the most influential authors, while Osteoporosis International and The Journal of Bone and Mineral Research were the most cited journals. Key themes included extracellular vesicles, romosozumab, bisphosphonates, and breast cancer, with recent attention on targeted drug delivery, treatment efficacy, and medication management. Emerging keywords from 2022 to 2023, such as exosomes, inflammation, and osteogenic differentiation, reflected advances in therapeutic mechanisms and clinical applications.ConclusionFuture research will likely emphasize targeted drug delivery, clinical efficacy and safety, and molecular targeted therapies, with the development of new anti-osteoporosis drugs remaining a key focus.